An exploratory analysis of infant and young child feeding perceptions and practices among South Asian women living in London - Ayesha Awal; Malika Al Kattan; Regina Keith Murphy (World Nutrition)
Background Breastfeeding and complementary feeding are crucial in early life nutrition. In the UK, only 1% of mothers exclusively breastfeed at six months. Data from England (2020-21) show that at six to eight weeks, breastfeeding rates were lower among white mothers (49.8%) than among Asian or Asian British mothers (69.0%). However, exclusive breastfeeding rates in the home countries of UK minority groups are higher than those of their counterparts in the UK. Objective This study explores the perceptions and practices of South Asian mothers in London regarding infant and young child feeding (IYCF), identifying socio-cultural and environmental influences. Methods A qualitative study recruited eleven South Asian mothers of children under five living in London through purposive convenience and snowball sampling. Semi-structured online interviews were conducted, and data were analysed following an inductive thematic approach. Results Three themes emerged: (1) maternal practices shaped by religion, culture, and social support; (2) lack of support in managing IYCF challenges; and (3) practical support needed to enhance exclusive breastfeeding: cultural and religious beliefs, emotional bonding, and convenience motivated breastfeeding initiation. However, mixed feeding and early solid food introduction occurred due to perceived milk insufficiency and misinformation. Mothers relied on social circles and digital sources due to cultural and language barriers. Inadequate maternity leave policies were perceived to lead to shorter breastfeeding durations, particularly among recent immigrants. Conclusions Addressing milk supply misconceptions and providing information on infant needs are essential. Policy changes offering flexible work conditions could support breastfeeding among immigrant mothers.